The circuit in urban etnomusicology - Soares, Nelson Souza (Laboratório Editorial Faculdade de Ciências e Letras, 2021)
The anthropological study in the urban scene has peculiarities in relation to studies carried out in traditional communities. In the urban landscape, groups are inserted in large contexts within complex networks with restrictions and meanings. José Guilherme C. Magnani (2005) intend a form of analysis in which he considers the social actors with their specificities and the space that they operate, the latter being a determining product and factor of social practice, and not a simple scenario. Magnani formulates categories of analysis based on this idea of considering space as an element that can be studied. In this paper we seek an analysis of the methodological contributions that the use of the concept of circuit can bring to urban ethnomusicological research, specifically on study of youth contexts involving popular music.